THEMATIC CLASSIFICATION OF GAME NAMES IN ENGLISH AND UZBEK LANGUAGES - Mengboyev Azizbek Alijon ugli (Western European Studies, 2025)
This article explores the thematic classification of game names in English and Uzbek languages, analyzing their semantic and cultural significance. It examines how the names of games reflect the social, cultural, and historical contexts of each language. The study categorizes game names into thematic groups such as traditional, modern, educational, and sports-related games, emphasizing similarities and differences between English and Uzbek linguistic patterns.
Keywords: game names; semantics; thematic classification; English